EFFECT OF IODINE ON NON-ENZYMATIC ANTIOXIDANT LEVELS OF GLYCINE MAX L. GROWN UNDER HEAVY METAL AND HEAT STRESS - Neha, Gupta (Innovare Journal of Sciences, 2016)
ABSTRACT Objective: The present research work was designed response of iodine on non-enzymatic antioxidant levels grown under heavy metal and heat stress in soybean. Methods: Soybean seeds exposed to different concentrations three of which were applied in increasing doses of IO3− (20, 40 and 80 µM as KIO3-) with Heavy metal and Heat stresses were subjected to analysis of non-enzymatic biochemical parameters including ascorbic acid, proline, glutathione, using the standard protocols. Results: The application of IO3− can improve the levels of non-enzymatic antioxidant levels to severe cadmium chloride and Heat stress in soybean seeds (Glycine max L). Our study recommends that IO3− could be considered a possible beneficial element to counteract the harmful effects of cadmium chloride and heat stress. Conclusion: Our study recommends that IO3− could be considered as a possible beneficial element to counteract the harmful effects of cadmium chloride and heat stress. Keywords: Glycine max L., Heavy metal stress, Heat stress, Ascorbic acid, Proline, Glutathione, Iodine